POSSIBILITIES FOR APPRECIATION OF CHILD PSYCHO-MOTOR AVAILABILITY WHO PRACTICING TABLE TENNIS (GYMNASIUM, 2017)
Starting from the idea that selection is essential for performance in table tennis we want to develop a set of tests by which we can investigate the general and specific motor possibilities of children, enriching in this way quantitative and qualitative the existing control samples and control rules. The recorded data in the two groups have confirmed the hypothesis, there was obvious differences in comparison of the proposed samples. Statistically, there were obtained values ​​"abnormal" and the index values ​​of "t" shows insignificant differences in the media. The set of tests proposed and applied on the experimental group has proven the validity highlighting the same motor indicators as in the control group. The recorded results from control sample that was propose in the new test highlights some functional possibilities of the sportsman who are not highlighted by applying in other types of tests.